Stockholdings of Officers and Directors in American Industrial Corporations - Gordon, R. A. (Quarterly Journal of Economics, 1936)
I. Nature of data and of sample: 1. The SEC data on stock ownership, 622; 2. Choice of companies in sample, 624; 3. Limitations of the data, 628. — II. Proportion of stock outstanding owned by management: 1. Percentage of stock owned by management groups, 631; 2. The relation between total percentage holdings and size of management groups, 633; 3. The relation between percentage holdings and size of company, 635. — III. The market value of stock owned by management: 1. Individual value-holdings of leading executives, 640; 2. Average value-holdings of management groups, 644; 3. The relation between average value-holdings and size of firm, 650. — IV. Summary and conclusions, 650.